2015
DOI: 10.1042/bst20140298
|View full text |Cite
|
Sign up to set email alerts
|

Bcl-2 and FKBP12 bind to IP3 and ryanodine receptors at overlapping sites: the complexity of protein–protein interactions for channel regulation

Abstract: The 12- and 12.6-kDa FK506-binding proteins, FKBP12 (12-kDa FK506-binding protein) and FKBP12.6 (12.6-kDa FK506-binding protein), have been implicated in the binding to and the regulation of ryanodine receptors (RyRs) and inositol 1,4,5-trisphosphate receptors (IP3Rs), both tetrameric intracellular Ca2+-release channels. Whereas the amino acid sequences responsible for FKBP12 binding to RyRs are conserved in IP3Rs, FKBP12 binding to IP3Rs has been questioned and could not be observed in various experimental mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 71 publications
0
18
0
Order By: Relevance
“…FK506, a calcineurin inhibitor, is a potent immunosuppressant for clinical prevention and treatment of allograft rejection (19–21). It exerts its immunosuppressive effect by binding to FK506 binding protein 12 (21, 22). Studies have shown that FK506 has neuroprotective and neurotrophic effects (23, 24).…”
Section: Introductionmentioning
confidence: 99%
“…FK506, a calcineurin inhibitor, is a potent immunosuppressant for clinical prevention and treatment of allograft rejection (19–21). It exerts its immunosuppressive effect by binding to FK506 binding protein 12 (21, 22). Studies have shown that FK506 has neuroprotective and neurotrophic effects (23, 24).…”
Section: Introductionmentioning
confidence: 99%
“…What is remarkable about these two signalling systems is the way they interact with each other [4] (figure 1 [9] and RYRs [10,11], is reduced by ROS [12]. ROS can activate a number of TRP channels that gate Ca 2þ (e.g.…”
Section: Integrated Calcium and Redox Signalling Pathwaysmentioning
confidence: 99%
“…One of the main functions of Nrf2 is to maintain the cellular level of the redox buffer GSH [136], which is a critical factor in preventing AD [44]. The level of Bcl-2, which inhibits the ability of InsP 3 to activate the InsP 3 receptors [9] and the RYRs [10,11] (figure 1), is maintained by Nrf2 and Klotho, thereby reducing the level of Ca 2þ . The ability of Bcl-2 to reduce the symptoms of AD in transgenic mice [137,138] may be explained by this reduction in the activity of both the InsP 3 R and RYRs.…”
mentioning
confidence: 99%
“…Molecular cloning of DmRyR cDNA provided the solid evidence of DmRyR expression in Drosophila lava [16]. As the crucial regulator of this CICR pathway along with binding protein of IP3R as well [47], in which four DmFKBP12 control opening of ER/SR DmRyR tetramer, the expression and function of DmFKBP12 should be carried out in the lava stage. Because of, as discussed above, RyR-mediated CICR exhibiting with calcium spark and calcium wave robusting from fertilization of many animals [4851], it is judicious that the DmRyR-FKBP12 complex functions as early as the same stage.…”
Section: Discussionmentioning
confidence: 99%